Gender, sex, and sexuality among contemporary youth : Generation Sex - Claster, Patricia Neff; Blair, Sampson Lee (Emerald Publishing Limited, 2017)
This volume examines the evolving norms concerning sex, gender, and sexuality in the lives of children and adolescents addressing topics such as: the development of gender identity, sexual behavior among youth, LGBT youth, transgendered youth, parental and peer influences upon the development of gender and gender identity and dating violence.
Keywords: Gender identity.; Gender expression.; Sex role.; Children -- Sexual behavior.; Teenagers -- Sexual behavior.; elektronické knihy; electronic books